2018
DOI: 10.5007/1980-0037.2018v20n4p517
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of weight excess in Brazilian children and adolescents: a systematic review

Abstract: The prevalence of obesity is rapidly increasing worldwide, no mattering age groups and socioeconomic status. In Brazil, it is still unclear the prevalence of obesity in children and adolescents, since most Brazilian studies have only verified regional prevalence of obesity. Therefore, the aim of the present study was to analyze the scientific production regarding the prevalence of weight excess in Brazilian children and adolescents. A search in the relevant electronic databases Medline/Pubmed, Web of Science, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
(22 reference statements)
1
12
0
3
Order By: Relevance
“…Studies suggest that the prevention of health and risk behaviors are related to the benefits of physical activity 19,24 , as the results observed in this study with boys, who were on average sufficiently active according to the physical activity recommendations 22 . However, when analyzing preventive behaviors and relationship patterns, an important aspect of this study, the findings showed that boys had negative attitudes toward these components.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Studies suggest that the prevention of health and risk behaviors are related to the benefits of physical activity 19,24 , as the results observed in this study with boys, who were on average sufficiently active according to the physical activity recommendations 22 . However, when analyzing preventive behaviors and relationship patterns, an important aspect of this study, the findings showed that boys had negative attitudes toward these components.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, Simões et.al. 22 reinforced the increase in prevalence of overweight in children and adolescents, highlighting the importance of preventive measures as well as therapeutic programs for a decrease in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…26 Therefore, as suggested by the present and previous studies, excess weight should be considered when looking at preventing hypertension development among youth, especially for Brazilian children and adolescents, which has an estimation of a quarter presenting excess weight. 27 By contrast, Yang et al, 28 highlight better levels of CRF associated with normal BP levels. Obese students with low CRF levels present a higher prevalence of hypertension (OR: 3.98; 95% CI: 2.92 to 5.41) compared to obese students with better CRF levels (OR: 1.75; 95% CI: 1.10 to 2.79), which suggests that CRF may attenuate the relationship between obesity and less favorable BP levels.…”
Section: Discussionmentioning
confidence: 96%
“…As medidas socioeconômicas avaliadas por esses estudos incluíram escolaridade dos pais 13,14,16,17 , renda familiar 15,17 e ocupação dos pais 16 . No Brasil, poucos estudos de abrangência nacional avaliaram o excesso de peso entre adolescentes 19 . Estudos prévios, realizados no país, verificaram diferenças entre o excesso de peso e a condição socioeconômica a partir de análises bivariadas e sugeriram uma associação direta conforme observado nos países em desenvolvimento [20][21][22][23] .…”
Section: Introductionunclassified